A personalized mobility based intervention to promote pro-environmental travel behavior. (November 2020) - Ahmed, Shiraz; Adnan, Muhammad; Janssens, Davy; Wets, Geert
Graphical abstract: Highlights: Pro-environmental travel potential in an individual mobility routine is detected. Mobility intervention based on Personalized Travel Plans is designed and implemented. Significant Reduction in car dependency and increment in active mobility is observed. PTP based intervention can be effective to promote sustainable travel at societal level. Abstract: The development of effective behavioral change strategies that will convince individuals to voluntarily switch to pro-environmental travel behavior is a core research area for transportation and environmental experts. Personalized travel planning (PTP) is considered as an effective approach that encourages individuals to adopt environmental-friendly travel choices. This paper describes the design and implementation of a PTP intervention that was developed based on the persuasive techniques and the stage model of self-regulated behavior change (SSBC). Based on the recorded travel diary of the individuals, web-based customized pro-environmental travel plans were suggested along with pro-environmental and pro-healthy impacts. The effectiveness was assessed by comparing the travel behavior along with consequences before and after the implemented intervention. Significant differences were observed in an individual travel behavior regarding car dependency and active mobility with an effect size of 0.28 and 0.45 (Cohen's d) respectively. On an average, 4.25 percentage points decrease in CO2 emission and 6.10 percentage point increase in physical activity level per individual was found due to their change in travel behavior. Stage analysis of the individual travel behavior revealed that the implemented PTP intervention triggers an individual's transition towards more action-oriented stages in this behavior change process. Based on the results, it is concluded that intervention is effective to promote pro-environmental and pro-healthy travel choices and can bring higher benefits when implemented on a broader level.